1980
DOI: 10.1161/01.cir.62.5.925
|View full text |Cite
|
Sign up to set email alerts
|

Provocation of coronary artery spasm by the cold pressor test. Hemodynamic, arteriographic and quantitative angiographic observations.

Abstract: In this study we attempted to determine if the cold pressor test, a known sympathetic reflexogenic stimulus, could precipitate coronary artery spasm. Thirty-five patients undergoing coronary arteriography for evaluation of chest pain syndromes were given the cold pressor test. During 1 minute of cold pressor stimulation, aortic systolic pressure increased 18.1 ± 9.7 mm Hg (mean ± SD) and heart rate did not change significantly. Focal coronary artery spasm was provoked in seven patients, each of whom had an ath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
2

Year Published

1982
1982
2000
2000

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(63 citation statements)
references
References 24 publications
1
58
0
2
Order By: Relevance
“…Although some studies have reported that cold pressor stimulation induced constriction of normal coronary arteries, 23 -24 the control subjects were not selected to have completely smooth coronary arteries without intraluminal irregularities. It has since been demonstrated that the cold pressor test dilates the epicardial coronary arteries in the absence of stenosis or luminal irregularities.…”
Section: Cold Pressor Test In Normotensive Subjects and Hypertensive mentioning
confidence: 99%
“…Although some studies have reported that cold pressor stimulation induced constriction of normal coronary arteries, 23 -24 the control subjects were not selected to have completely smooth coronary arteries without intraluminal irregularities. It has since been demonstrated that the cold pressor test dilates the epicardial coronary arteries in the absence of stenosis or luminal irregularities.…”
Section: Cold Pressor Test In Normotensive Subjects and Hypertensive mentioning
confidence: 99%
“…After control recording of hemodynamics (heart rate, systemic arterial and left atrial pressure) and determination of regional myocardial blood flow, i.v. norepinephrine, [6][7][8][9][10][11][12][13][14] ,ug/min, was infused to increase mean arterial pressure approximately 20 mm Hg above control levels so as to mimic the blood pressure increase (15-20 mm Hg) in humans subjected to cold pressor stress.5 6 After 10 minutes, hemodynamics were recorded, a second injection of radiolabeled microspheres was performed, and the infusion was then discontinued. After the pig had recovered for 20-30 minutes, hemodynamics were again recorded and microspheres again injected to determine regional myocardial blood flow.…”
Section: Animal Preparationmentioning
confidence: 99%
“…77' 78, 80 The region of decreased flow has even been localized to the region of atherosclerotic narrowing in some patients.79 81 Administration of the a-receptor-blocking agent phentolamine blunts the coronary vasoconstriction in patients with angina.77 fl-Receptor blockade with propranolol potentiates the cold pressor vasoconstrictor response.80 Although the cold pressor test can elicit spasm in some patients with variant angina, narrowing of coronary stenoses in patients not thought to have variant angina was observed in several cases. 82 Taken together, these studies suggest that placing a patient's hand in ice water elicits a reflex a-receptor-mediated coronary vasoconstriction that in some patients results in supercritical narrowing of a stenotic arterial segment, which can lead to reduced flow despite tachycardia and an increase in blood pressure. a-Blockade.…”
mentioning
confidence: 82%
“…No. 4, October 1987 with coronary sinus thermodilution during cold pressor tests, and in patients without significant coronary artery disease the expected increase in coronary blood flow secondary to the increase in myocardial metabolism is observed.77 81 Angiographic analysis of normal segments of arteries during a cold pressor test indicates there is a generalized vasoconstrictor response in large 82 coronary arteries.…”
mentioning
confidence: 99%